2017
DOI: 10.1186/s13705-017-0110-7
|View full text |Cite
|
Sign up to set email alerts
|

The production of hydrogen as an alternative energy carrier from aluminium waste

Abstract: Background: Aluminium dross is a valuable resource that is often redirected to landfill as there are no real viable solutions for the utilisation of this industrial waste. A study has been conducted to provide a recycling process where the dross is reacted with an alkaline solution in order to generate hydrogen with bayerite and gibbsite products. Methods: Samples of aluminium dross were obtained from two sources: aluminium dross obtained from an aluminium recycling facility, recycled dross (RD) in Qatar and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…from soft drink cans for obtaining hydrogen in the presence of sodium hydroxide [22,23]. Also, heavily adulterated scrap aluminium, which is not suitable for recycling and secondary aluminium production can be used for hydrogen production [24]. However, aluminium alloy composition may have an influence on the conversion degree [10].…”
Section: Production Of Hydrogen From Aluminiummentioning
confidence: 99%
“…from soft drink cans for obtaining hydrogen in the presence of sodium hydroxide [22,23]. Also, heavily adulterated scrap aluminium, which is not suitable for recycling and secondary aluminium production can be used for hydrogen production [24]. However, aluminium alloy composition may have an influence on the conversion degree [10].…”
Section: Production Of Hydrogen From Aluminiummentioning
confidence: 99%
“…Therefore, H 2 gas generation from the hydrolysis of SC in MSW landfills poses a particular concern from an engineering control perspective. On the other hand, it became a useful approach and opportunity to generate hydrogen from aluminum wastes as a new source of energy (David and Kopac 2012;Elsarrag et al 2017;Hiraki et al 2007;Huang and Tolaymat 2015;Li et al 2017;Shkolnikov et al 2011).…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…Instead of using chemical promoters, such as hydroxides, oxides, or salts, the authors of [5] dealt with ball milling as a pretreatment and carried out the reaction in hot water. In [6], the difference between Al dross obtained from an aluminum recycling facility (RD) and Al dross directed to landfills (LD) was studied. The authors reported that, with NaOH as the promoter, the RD and LD samples generated 0.50 and 0.15 L of H 2 per 1g of Al, respectively.…”
Section: Introductionmentioning
confidence: 99%